2018
DOI: 10.1021/acs.energyfuels.8b01131
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Property–Performance Analysis for CO2-Philic Foam-Assisted CO2-Enhanced Oil Recovery

Abstract: Foam is used in CO2-enhanced oil recovery due to its potential high benefits in mitigating all three causes of CO2 poor sweep efficiency, as it provides a means to lower the effect of permeability heterogeneity, overcome viscous instability, and minimize the occurrence of gravity override. The conventional foaming surfactants are not suitable in contact with oil due to premature lamellae rupture, need for copious amounts of water to generate foam, surfactant loss due to adsorption on the rock or partitioning b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…They need the Isopropyl acetate molecule as a sample. In the picture below, the red colour imitate oxygen, black represents carbon and white is used for atoms of hydrogen [7,[30][31][32][33][34].…”
Section: Co 2 -Philic Surfactants For Foammentioning
confidence: 99%
See 1 more Smart Citation
“…They need the Isopropyl acetate molecule as a sample. In the picture below, the red colour imitate oxygen, black represents carbon and white is used for atoms of hydrogen [7,[30][31][32][33][34].…”
Section: Co 2 -Philic Surfactants For Foammentioning
confidence: 99%
“…A series of trials was conducted by Matthew B. Miller* by the mixing of different solvents with various extents of carbon dioxide to measure the compatibility for both mixture components having bubble point as basis. It is observed that species with low MM (molar mass) having minimum one atom of O 2 in ether, acetate groups/or carbonyl would have most favourable interaction with carbon dioxide through Lewis base/Lewis acid interactions [7].…”
Section: Molecular Weightmentioning
confidence: 99%
“…Moreover, Ren et al , and Zeng et al demonstrated that gravity segregation between phases in a homogenous reservoir could be better mitigated by novel foams. Experimentally, a correlation was derived by Talebian et al , to indicate the variation of foam model parameters with CO 2 -philic surfactant chain lengths during the EOR process.…”
Section: Introductionmentioning
confidence: 99%
“…Supercritical carbon dioxide (scCO 2 ) has attracted tremendous attention in organic synthesis, extraction, oil industry, and other fields due to its intrinsic properties (e.g., low cost, nontoxicity, stability, and abundance). However, the CO 2 molecule can only be dissolved in nonpolar substances due to its linear configuration. In contrast, scCO 2 has extremely low solubility in polar substances such as biomolecules, polymers, ions, and water, greatly limiting the development and application of scCO 2 .…”
Section: Introductionmentioning
confidence: 99%